1991
DOI: 10.1128/jb.173.7.2167-2172.1991
|View full text |Cite
|
Sign up to set email alerts
|

Multiple determinants of functional mRNA stability: sequence alterations at either end of the lacZ gene affect the rate of mRNA inactivation

Abstract: The Escherichia coli lacZ gene was used as a model system to identify specific sequence elements affecting mRNA stability. Various insertions and substitutions at the ribosome-binding site increased or decreased the rate of mRNA inactivation by up to fourfold. Deletion of a dyad symmetry, which may give rise to a very stable secondary structure in the mRNA immediately downstream of the gene, decreased the functional stability of the lacZ message. The magnitude of the latter effect was strongly dependent on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…The rates of decay of several bacterial transcripts, including ompA, lacZ, and ermC, are controlled by determinants located at the 5' ends of the mRNAs (2,3,5,12,29,30). Decay is initiated at the 5' ends of some transcripts, for example, lacZ and ompA (6,23,24).…”
mentioning
confidence: 99%
“…The rates of decay of several bacterial transcripts, including ompA, lacZ, and ermC, are controlled by determinants located at the 5' ends of the mRNAs (2,3,5,12,29,30). Decay is initiated at the 5' ends of some transcripts, for example, lacZ and ompA (6,23,24).…”
mentioning
confidence: 99%
“…Previous studies have reported that various insertions and substitutions at the RBS affect the rate of mRNA degradation (30) and that the hairpin structures impart stability to selected regions of polycistronic mRNAs (12). However, Northern blot analysis of total cellular RNA isolated from strains containing the six operon with the RBS and STL mutations showed that there was no effect on the steadystate level of six mRNA.…”
Section: Discussionmentioning
confidence: 69%
“…Several studies demonstrated that mRNA leader segments confer stability to otherwise labile transcripts (Yamamoto & Imamoto, 1975;Gorski et al, 1985;Belasco et al, 1986;Gerdes et al, 1988;Rdgnier & Grunberg-Manago, 1990;Petersen, 1991). The ompA leader has been shown to stabilize efficiently a downstream bla message fused to it; interestingly, this stabilization required both the presence of an upstream segment of the ompA leader, which contains secondary structures, and tr'anslation of the bla message from the ompA ribosome-binding site (Belasco etal., 1986;Emory & Belasco, 1990).…”
Section: The Endonucleolytic Decay Of Mrna" the Importance Of 5~-termentioning
confidence: 96%
“…For such a reason, the segment corresponding to the lacZ message was more stable than the downstream lacY message, and it was inactivated predominantly by endonucleolytic attacks occurring near the ribosome-binding site. The general model of mRNA inactivation derived by Petersen (1991) also implies that chemical mRNA decay, endoribonucleolytic or exoribonucleolytic, depends on the presence and distribution of endonucleolytic target sites and protective RNA secondary structures at the 3 ~ end. In 1982 Higgins et al identified a novel intercistronic regulatory element of prokaryotic operons: the repetitive extragenic palindromic (REP) sequence.…”
Section: Current Models Of Mrna Processing and Decay Of Polycistronicmentioning
confidence: 99%